WASTE GLASS MANAGEMENT FOR BAKIRKOY MUNICIPALITY: A CASE STUDY - Pir, Anil; Apaydin, Omer (YILDIZ TECHNICAL UNIV, 2015)
District municipalities in metropolitan cities are in indispensable position on separate collection of wastes, collecting waste from site and transporting those to disposal or recycling facilities in Turkey. By building correct and effective system of collecting wastes, separately collected waste fraction and quality of these wastes will increase moreover both costs of collecting from sites and separating in facilities will be lowered. In the country, waste glasses are collected from door to door with other recyclable wastes by many municipalities. In case of collection and separation of waste glass together with other packaging wastes, occupational accident risks increase. On the other hand, if they involved in municipal wastes, waste glass is being embedded into disposal areas and becomes harmful for habitat. Bakirkoy, a district of Istanbul city has 220,663 population and production of municipal solid waste is 326.5 tones daily in it. 5 % of these wastes are composed of glass. Within the scope of this paper; legislations about recyclable waste management in Turkey are examined, commonly used waste collecting systems are researched, existing equipment locations are optimized and by determining needed equipments to collect waste glass with stationary container system from the town they are marked onto the map considering accessibility by the local community, with CAD (Computer-Aided Design) software. Consequently, it's been deduced that 95 new collection locations should be added out of 45 old ones. Furthermore, the application has been monitored for 18 months. By increasing the number of waste glass bins and planning their dispersion on site, recovered glass amount have raised outrageously, on the other hand people's interest and consciousness about recycling of waste glass has begun to increase as well.
Keywords: Municipal solid waste; recycling; waste collecting systems; waste glass; waste management; Engineering